THE STRATEGY DEVELOPMENT OF THE REGION: THE PECULIARITIES OF THE INNOVATIVE MODELS’ FORMATION - V. V. Biryukova; V. V. Biryukov; E. V. Romanenko (Вестник СибАДИ, 2018)
Background. The author’s vision of the strategy selection process, according to which external and internal development conditions of the region provide  the possibility to obtain a sustainable competitive advantage in the adequate  territorial innovation models’ formation is presented in the article.Methods. The methodology as a synthesis of the systemic, evolutionary and spatio-temporal approaches is developed. The systematic approach allows to  explore the organizational and institutional region structure, which elements  are interrelated and complemented to each other. The evolutionary approach for understanding and assessing the internal system dynamics, the relationship between actors and basic units in evolutionairy internal and  external environment is used. The space-time approach involves the usage of multidimensional spatial-temporal coordinates. Conclusions. The main types of the innovative territorial models are highlighted. The features of the essential elements’ formation and the  innovative infrastructure’s relations are revealed. The holistic vision of the  territorial innovation models’ formation problem is proposed. The process of a center-peripheral mechanisms forming with the different regional  innovation potential is considered. Also the features of their place and role  formation in the process of generating and using knowledge and technology  are identified. The article show that the innovation strategy development is  an effective way of the competitive advantages’ development in the territories, the need for storage and the constant search for new knowledge,  as well as the successful adaptation to the changing business environment are also proved in the research. The necessity to develop the  innovative strategies based on the of territorial innovation models’ individualization and on the regional context is substantiated in the article.Practical importance. The definiteness to the states of the research could be used as a theoretical model which defines the interrelations between  factors and variables. It is possible to develop specific hypotheses about the success of the innovation strategy basing on this model.